IMPLEMENTASI NILAI-NILAI ISLAM OLEH GURU: TANTANGAN DAN STRATEGI DALAM PEMBENTUKAN KARAKTER SISWA - Jamaluddin, Ahmad; Darman, Muhammad Hikam; Tacong, Kamaluddin; Sulaiman, Umar; Achruh, Andi (Prodi PGMI IAI Sahid, 2026)
This study aims to examine the application of behaviorist theory in improving students' basic discipline and cognition in science learning in elementary school. The method used is library research, by collecting and analyzing various written sources such as books, scientific journals, articles, and other publications relevant to the topic. The theory of behaviorism was chosen because it emphasizes the formation of behavior through stimulus and response, which is considered effective in building disciplinary habits and strengthening students' basic understanding of science concepts. The research process is carried out by examining relevant sources, recording the main principles, and comparing the views and findings of various authors. The results of the study show that behaviorism-based learning strategies, such as positive reinforcement, punishment, and repetitive exercises, can help students develop disciplined behaviors and improve their conceptual understanding of science. These findings are expected to be a reference for teachers and education practitioners in designing more effective and theory-based learning approaches.